Hybrid electric vehicle system modeling and control - Liu, Wei, 1960 August 30- (Wiley, 2017)
Intended to contribute to a better understanding of hybrid electric vehicle systems, this thorough reference presents all the major aspects of hybrid vehicle modeling, control, simulation, performance analysis, and preliminary design. -- Edited summary from book.
Revised edition of: Introduction to hybrid vehicle system modeling and control.
Keywords: Hybrid electric vehicles -- Simulation methods.; Hybrid electric vehicles -- Mathematical models.; elektronické knihy; electronic books